Heartworn highways [videorecording (DVD)] - Van Zandt, Townes; Clark, Guy; Young, Steve, 1942-2016 (Kino Lorber, 2021)
Sometimes, a documentary filmmaker is present at precisely the right moment to capture lightning in a bottle. It happened with Bob Dylan in Don₂t Look Back, Chet Baker in Let₂s Get Lost, and it happened with 1976₂s Heartworn Highways. This iconic outlaw country documentary saw filmmaker James Szalapski travel to Texas and Tennessee to capture the radical artists reclaiming the genre by rejecting the mainstream Nashville machine. The hard-living, and hard-partying, lifestyles of the outlaw country₂s figureheads are played out on screen as we visit Van Zandt₂s Austin trailer, see Coe play in Tennessee State Prison, join the gang in Nashville₂s notorious Wig Wam Tavern and witness a liquor-fueled Christmas at Clark₂s house. No wonder the film₂s original tagline read: ₁The best music and the best whiskey come from the same part of the country.₂ Outside of a couple of festival screenings, the movie remained unreleased for five years after its completion, finally hitting screens in 1981. It has been building a cult audience ever since. Light in the Attic Records